Genocide a comprehensive introduction - Jones, Adam 1950- (Routledge, Taylor & Francis Group, 2024)
"Genocide: A Comprehensive Introduction is the most wide-ranging textbook on genocide yet published. Designed as a text for undergraduate and graduate students from a range of disciplines it will also appeal to non-specialists and general readers"--
"First edition published by Routledge 2006. Second edition published by Routledge 2010. Third edition published by Routledge 2017"--t.p. verso
Keywords: Geschichte; Völkermord; Genocide; Lehrbuch